Maternal immunisation: ethical issues. Issue 12 (December 2016) - Verweij, Marcel; Lambach, Philipp; Ortiz, Justin R; Reis, Andreas
Summary: There has been increased interest in the potential of maternal immunisation to protect maternal, fetal, and infant health. Maternal tetanus vaccination is part of routine antenatal care and immunisation campaigns in many countries, and it has played an important part in the reduction of maternal and neonatal tetanus. Additional vaccines that have been recommended for routine maternal immunisation include those for influenza and pertussis, and other vaccines are being developed. Maternal immunisation is controversial since regulators, professionals, and the public are often reluctant to accept pharmaceutical interventions during pregnancy. So far, little attention has been given to the ethics of vaccination during pregnancy. In this Personal View we argue that maternal immunisation should be offered in response to concrete, severe risks of disease for mother and child, and we explain how this requirement of serious risk can be used to guide ethical decision-making about maternal immunisation.